A Geometric Look At Repeated Measures Design with Missing Observations - Alwi, Ahmad; Monlezun, C. J. (1984)
In this paper, we will provide a geometric view of Repeated Measures Design for unequal number of subjects per treatment that has missing observations. For our geometric development we restrict our design to three levels of factor A and four levels of factor B. The purpose of this paper is to develop a test statistics for hypotheses of interest i.e. no main effect A, no main effect B, and no AB interaction.